Evaluation of a unified p-y method for lateral analysis of large-diameter drilled shafts using NVShaft. (September 2022) - Bhuiyan, Fahim M.; Motamed, Ramin; Siddharthan, Raj V.; Sanders, David H.
Graphical abstract: Highlights: A unified p-y method incorporating side shear-induced moment and tip resistances in the beam on nonlinear Winkler foundation model is introduced. A finite-difference program, NVShaft, that implements unified p-y analysis is proposed. Data collected from two different load test programs are used to evaluate NVShaft predicted response. A parametric study on diameter effect further emphasizes the role of additional lateral resistance components on the large-diameter drilled shaft. Abstract: Lateral load analyses of large-diameter drilled shafts based on the conventional p-y method tend to result in unreliable responses. The paper highlights a unified p-y analysis that incorporates vertical side shear-induced moment and tip resistances, which becomes significant in laterally-loaded large-diameter drilled shafts. A simplified tip moment resistance model applicable to any well-defined soil or rock material is also proposed. To perform unified p-y analysis, a finite-difference-based comprehensive load analysis program, NVShaft, has been developed. The lateral shaft response using NVShaft was evaluated using two field load tests from Las Vegas in cemented soil, and two field load tests in sand and clay dominant sites from the PISA project in Europe. Comparison between measured responses and numerical predictions signifies the relative importance of added resistance components in the unified p-y analysis in different subsurface materials. Further investigation on diameter effects in the context of mentioned load test programs indicates that additional lateral resistance in large-diameter shaft comes mostly from side shear-induced resisting moment, followed by tip shear resistance.